A multifunctional cobalt–organic framework for proton conduction and selective sensing of Fe3+ ions. Issue 14 (14th March 2023) - Zhang, Wen-Sha; Wang, Guang-Qing; Wang, Yu-Xin; Yang, Yan-Li; Bai, Xue; Cui, Hong; Lu, Ying; Liu, Shu-Xia
Abstract : A cobalt-organic framework was synthesized successfully and it shows both remarkable proton-conductive ability and fluorescence sensing performance towards Fe 3+ ions. Abstract : Developing multifunctional metal–organic frameworks (MOFs) is a new research trend. MOFs have shown remarkable performances in both proton conduction and fluorescence sensing, but the MOFs integrating the two performances are scarce. Herein, a Co-MOF, [Co6 (oba)4 (Hatz)(atz)(H2 O)2 (μ3 -OH)2 (μ2 -OH)]·H2 O (1, H2 oba = 4, 4-oxybis(benzoic acid), Hatz = 5-amino-1 H tetrazole), has been assembled by Co 2+ ions with H2 oba and Hatz ligands, providing a unique example of multifunctional MOFs with both proton conduction and fluorescence sensing performances. The framework of 1 displays a pillar-layer structure built by the oba ligand as a pillar and a layer composed of Co-clusters and atz linkers. Because large-scale single crystals of 1 were successfully synthesized, the proton conduction ability of 1 was investigated using single crystal samples. 1 exhibits highly anisotropic conduction with conductivity values of 1.1 × 10 −3 S cm −1 along the [001] direction and 9.1 × 10 −6 S cm −1 along the [010] direction at 55 °C and 95% RH, respectively. Meanwhile, the fluorescence sensing of 1 towards metal ions was studied in aqueous solutions. Attractively, 1 may sensitively and selectively detect Fe 3+ ions in the presence of other interfering ions by fluorescence quenching.